To solve this, simply switch the X and y variables within one equation, and upon doing so, see and check if it equals to the other equation.
f(X) = -X + 4/5
Y = -X + 4/5
X = (-Y+4)/5
5X = -Y + 4
-Y = 5X - 4
Y = -5x + 4
Yes, by looking at the second equation it is an inverse of the first one.
Answer:
12
Step-by-step explanation:
There are 4 circles, 6 stars. The ratio is 4/6 = 2/3
if there is 8 circles in order to get the same ratio 8/x = 2/3 => x = 12
Answer:
D
Step-by-step explanation:
its the closest to the answer i got so that must be it
Answer:
250
Step-by-step explanation:
Answer:
1 hour and 50 minutes will take to fill up a 300 gallon swimming pool explanation just do the quation/math